PENGARUH PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Maliah Maliah; Sahila Sahila; Liliana Liliana (Jurnal RATRI (Riset Akuntansi Tridinanti), 2022)
This study aims to determine the effect of Return on Equity (ROE) and Earning per Share (EPS) simultaneously on  stock  prices  in  banking  sub-sector companies  listed  on  the  Indonesia  Stock Exchange (IDX). The method used in this study is associative and uses a quantitative approach. The sample in this study is 43 banking companies listed on the Indonesia Stock Exchange in 2017-2019 (43x3=129 samples). The data analysis technique used in this research is  descriptive statistics, normality test, classical assumption test, multiple linear regression, coefficient of determination, t test, f test using the software program spss 22 for windows. From the results of the t-test research shows that Return on Equity (ROE) has an effect on stock prices in banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) because the significant value is 0.006 <0.05. Earning per Share (EPS) has an effect on stock prices in banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) because the significant value is 0.000 <0.05. Return on Equity (ROE) and Earning per Share (EPS) have a simultaneous effect on stock prices in banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) because the significant value is 0.000 <0.05.Keywords : Stock Price, Return on Equity and Earning per Share